#Nitrosocarbonyls 1: Antiviral Activity of N-(4-Hydroxycyclohex-2-en-1-yl)quinoline-2-carboxamide against the Influenza A Virus H1N1. (30th December 2014) - Al-Saad, Dalya; Memeo, Misal Giuseppe; Quadrelli, Paolo
Abstract : Influenza virus flu A H1N1 still remains a target for its inhibition with small molecules. Fleeting nitrosocarbonyl intermediates are at work in a short-cut synthesis of carbocyclic nucleoside analogues. The strategy of the synthetic approaches is presented along with the in vitro antiviral tests. The nucleoside derivatives were tested for their inhibitory activity against a variety of viruses. Promising antiviral activities were found for specific compounds in the case of flu A H1N1.